Backward Integration as a Business Strategy to Increase Company Profitability - Pratama Napitupulu, Binsar Energia (Journal of World Science, 2022)
PT. Graha Alam Indo Sentosa is a developer operating in the real estate industry. Budiman Napitupulu and his son Binsar Napitupulu founded the company in 2017 in Semarang, Central Java. The organization prefers to construct housing zones for low- to middle-income people. The program is known as "Perumahan Bersubsidi." PT. Graha Alam Indo Sentosa is in the process of constructing a residential community (Perumahan the Sambeng Village) in Pemalang Regency, Central Java. The overall area to be developed is 5,6 hectares and will feature around 530 homes and 37 stores. The developer has built and sold 220 residences and five shops as of November 2021. As part of its backward integration business strategy, PT Graha Alam Indo Sentosa owned the business unit Sambeng PreCast in order to reduce construction costs. The business unit is intended to assist the corporation in generating the building materials needed to create houses, roads, and water channels. This research will elaborate on the success of the backward integration approach and whether or not it can significantly contribute to the company's sales and profits. Based on the discussion in the all chapters available (business exploration, business solution,and financial analysis), profitability has been positively benefited by the backward integration business plan followed by PT Graha Alam Indo Sentosa via the business unit (Sambeng PreCast). Using a backward integration strategy, the corporation can reduce building costs (COGS) and improve revenues and profits automatically. So, the company is advised to continue or even expand the backward integration business strategy.